Controlled Release of Natural Antibacterial Drug Loaded by Silk Biomaterials (Journal of Fiber Bioengineering and Informatics, 2018)
A significant challenge still remains for the development of drug delivery system (DDS) using herbalmedicine for clinical applications. The present study describes a novel DDS consisting of a naturalantibacterial drug berberine and silk fibroin (SF) for controlled drug delivery application. Compositefilms were synthesized using of SF and berberine mixtures at varied ratios. The unique structuralfeatures of SF molecules were analyzed using Fourier transform infrared spectroscopy (FTIR) anddifferential scanning calorimetry (DSC) during different film processing and post-processing conditions.Results revealed that water-annealed and glycerol modified method accurately controlled crystallizationvia modification of the secondary structure of the SF matrix and interaction with the non-crystallinedomains, resulting in control of film degradation as well as drug diffusion rate. A linear relationshipbetween crystallinity content (beta-sheet dominated silk II structure) and the release of entrappedberberine was achieved. The initial antibacterial activity of berberine retained for 4 days. The stabilityof the drug in SF film enhanced the intermolecular interactions between SF and berberine molecules. Inconclusion, the composite materials consisting of SF and berberine have a great potential application asa DDS providing antimicrobial activities, such as antimicrobial suture and biomedical textiles.
Keywords: Silk fibroin; Berberine; Film; Antibacterial; Drug delivery system